Development of Reginal Tourism Based on the Perspective of New Public Management Theory - Yujia, Gong; Niyomyaht, Satit; Kalyanamitra, Kamolporn; Siriphornwut, Nattawat (Asia Pacific Journal of Religions and Cultures, 2024)
The research objectives were: (1) to study regional tourism, (2) to study the role the government played in global tourism, (3) to study the current situation of regional tourism in Guangdong Province, and (4) to study the current problems of regional tourism in Guangdong Province. This research was qualitative. The key informants were 20 by a purposive selection from the personnel related to the domestic tourism industry, a government agency member. The research tool was an interview form. The statistical analysis was a descriptive method. The research found that: (1) regional tourism was a complete tourist destination, with tourism as a dominant industry in the region, unified layout planning, overall marketing and promotion, comprehensive overall management, and optimization of public services. Then promote the transformation of tourism in the past single scenic spot construction and management mode to achieve the quality, modernization, internationalization, and intensive development of tourism. (2) the role the government played in global tourism was considering the definition of regional tourism and government functions, the development of regional tourism is a new type of regional development. (3) The current situation of regional tourism in Guangdong Province at present, there were two 5A-level tourist attractions and 31 4A-level tourist attractions on the coastline of Guangdong Province. Among them, Shenzhen coastline tourism was the most developed, with the highest product quality, with a 5A, 4A tourist attractions. And (4) to study the current problems of regional tourism in Guangdong Province found that the weak service function of government project planning， lack of standardization of the utilization of government resources, the overall tourism infrastructure was not perfect, the coordination between the departments involved in regional tourism was not in place， the government supervision and supervision mechanism needed to be improved， the means of overall tourism marketing was single.